A modeling study with 4th graders - Celalettin Çelebi; Fatih Yılmaz; Yakup Yılmaz (Institute of Advanced Engineering and Science, 2024)
People need effective writing skills to successfully maintain their personal development and academic life. This research studies, the correlations among primary school 4th graders’ writing anxiety, writing attitude, and writing self-efficacy. The research has been designed in the correlational survey model; and a total of 255 primary school 4th-grade students, 95 male and 160 female, participated voluntarily in the research. Three psychometric tools have been used for data collection. Due to small number of participants, the data have been analyzed using the partial least squares structural equation modeling. According to the results, primary school 4th-grade students’ writing attitude does not significantly affect writing anxiety (H1). Moreover, writing self-efficacy does not have a significant effect on writing anxiety (H2) as well. However, writing self-efficacy significantly affects writing attitude (H3). The success of writing depends on the students’ writing self-efficacy, attitude towards writing, and writing anxiety. In order for successful writing, the level of self-efficacy should be high, the attitude towards writing should be positive and there should be no anxiety about writing.